Adaptive capacities and social resilience on Kangaroo Island: Beyond the staples trap. (3rd May 2021) - Argent, Neil
Abstract: This article uses the lens of evolutionary economic geography to consider adaptive capacities and forms of social resilience that manifest in rural, primary commodity‐dependent regions in the face of structural forces to which such regions seem predisposed. Using a case study of Kangaroo Island, South Australia, the article explores the demographic and social impacts that a sudden and dramatic commodity market collapse in the 1990s had on this rural economy and community and on its regional development. During late 2017 and early 2018, semi‐structured interviews were conducted with six representatives of the Kangaroo Island business community, including those from the farm, tourism, and small business sectors (three interviews) and from local government (one interview), as well as with a former rural financial counsellor and the former Commissioner for Kangaroo Island. Although the collapse of the wool market and of a flawed managed investment scheme for agroforestry had dramatically negative impacts on local economic and social systems, the Island's subsequent demographic recovery and Islanders' ongoing commitments to their sporting clubs both point to considerable adaptive capacities and social resilience. The research highlights what can be achieved by people with high levels of place attachment and commitment, as individuals and as collectives also able to draw on support scales beyond the local.